An exploitation area of Szlachtowa ore as an element of the future Pieniny Geopark - Bartuś, Tomasz; Kuś, Tomasz (Geotourism/Geoturystyka, 2025)
One of the most interesting objects of the future Pieniny geopark would be the Jarmuta and Pałkowski stream adits. Traces of the mining heritage of an exploitation area of Szlachtowa ore are characterized by high scientific, historical, educational and cognitive values. The extraction of ore minerals which took place probably from XIV to XVIII century was connected with presence of polymetallic veins and hydrothermal processes around the andesite intrusions of the Eastern Polish part of the Pieniny Andesite Line (PAL). Historical mines exploited epithermal, poor gold- silver deposites. The land use within the Pieniny Geopark might contribute to reduction in tourist flows in the most popular and crowded parts of the Pieniny Mts.